A Gravity Model Analysis of the Influencing Factors of Ghana-Nigeria Bilateral Trade in Merchandize Products - Abasimi, Ignatius; Salim, Agus (Universitas Ahmad Dahlan, 2022)
Evidently, the quantum of the general and sectoral impacts of growing trends of Ghana- Nigeria bilateral trade has been a phenomenon of mixed feelings. To some analysts the relationship has been positive, to others it is challenging. The purpose of this research therefore, tries to evaluate the influencing factors of Nigeria-Ghana trade in merchandize products through the gravity model of trade from 2008-2019. The results showed that the real exchange rate had a small but significant positive impact on the bilateral trade between Ghana and Nigeria, but more importantly, it had a positive impact on the Nigerian economy. The study again discovered a positive correlation between the size of the economy between Ghana and Nigeria and the flow of bilateral trade. This shows that trade improves as the GDP between these two countries increases or decreases. The market size or population of both countries exhibited a strong positive impact on trade flows and this is consistent with the theoretical foundation. The study is unique because it is the first to exclusively study and empirically investigate the trend of Nigeria-Ghana bilateral trade relation through the Newtonian gravity model.